Anaphylactic Reaction by Local Anesthesia; Knowledge and Attitude among the Dental Practitioners - Muhammad Umair, Abdul Manan Shahid, Muhammad Muddassar, Maria Rabbani, Muhammad Rizwan, Sadia Rashid (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the knowledge and attitude of dental practitioners of Islamabad and Rawalpindi about anaphylactic reaction seen in patients after administration of local anesthesia. Method: A questionnaire based cross section study was conducted among the randomly selected practicing general and specialist dental surgeons of Islamabad and Rawalpindi during January to June 2022. About 370 questioners were prepared and distributed among the practicing dentist surgeons of Rawalpindi and Islamabad without any priority or preference of the area. Two dentists were nominated for distribution and motivation of participating dentists to fill the form and collect the filled forms after one week time or earlier. Results: Two hundred thirty dentists responded to the questionnaire. The results indicated that the majority of the participants had knowledge of one or more symptoms relating to anaphylaxis. However, none of the participants demonstrated that they knew about all symptoms relating to anaphylaxis. Only few had experience of managingthe reaction. The results also did not vary with age. About 75% dental surgeons knew about the emergency drug but about 40% of them were equipped with emergency kits in their clinic and knew the technique of use of it. Conclusion: Local Anesthesia is routinely used for various treatments by the dental surgeons and Anaphylactic reaction from it can happen anytime with any patient putting life on risk. To deal with such situation and protect the community, serious attitude is necessary. Presentstudy has revealed the lack of knowledge among dentists in Islamabad and Rawalpindi about anaphylactic reactions and theirattitude towardsmanagement which needs to be enhanced to prevent severe consequences on health and safety of common people seeking dental treatment. Our study will provide awareness to dentists to increase their knowledge and skills to deal such situations so that the community should proceed to the dentist for treatments with confidence of safety and better care. Keywords: Anaphylaxis, Allergy, Emergency drugs, Local Anesthesia